2020
DOI: 10.3390/ijerph17062116
|View full text |Cite
|
Sign up to set email alerts
|

An Estimated Structural Equation Model to Assess the Effects of Land Use on Water Quality and Benthic Macroinvertebrates in Streams of the Nam-Han River System, South Korea

Abstract: The extent of anthropogenic land use in watersheds determines the amount of pollutants discharged to streams. This indirectly and directly affects stream water quality and biological health. Most studies have therefore focused on ways to reduce non-point pollution sources to streams from the surrounding land use in watersheds. However, the mechanistic pathways between land use and the deterioration of stream water quality and biological assemblages remain unclear. This study estimated a structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Meanwhile, the land use type of this catchment was mainly grassland and woodland (>0.85), and the impervious ground area only accounted for a small proportion (<0.01). This is in accord with that agriculture land and urban land were negatively correlated with surface water quality, whereas forested land, water area, and grassland were positively correlated with water quality (Chen et al, 2016;Lee et al, 2020;Xu et al, 2019a). The PPI was relatively high (>0.09), and the secondary industry was underdeveloped (PSI was approximately equal 0.37).…”
Section: Analysis Of Main Controlling Factors Of Temporal Variation Of Nh 3 -N and Tpsupporting
confidence: 83%
“…Meanwhile, the land use type of this catchment was mainly grassland and woodland (>0.85), and the impervious ground area only accounted for a small proportion (<0.01). This is in accord with that agriculture land and urban land were negatively correlated with surface water quality, whereas forested land, water area, and grassland were positively correlated with water quality (Chen et al, 2016;Lee et al, 2020;Xu et al, 2019a). The PPI was relatively high (>0.09), and the secondary industry was underdeveloped (PSI was approximately equal 0.37).…”
Section: Analysis Of Main Controlling Factors Of Temporal Variation Of Nh 3 -N and Tpsupporting
confidence: 83%
“…Urbanized areas, including cultivation areas in the Nam-Han River Basin are concentrated downstream, and cover approximately 24% of the total area. Furthermore, forests cover approximately 70% of the total area of the basin [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al [ 25 ] evaluated the mechanistic pathways between land use and the deterioration of both stream water quality and biological assemblages using a structural equation model (SEM), reflecting the impact of agricultural and urban land use on water quality and the benthic macroinvertebrate index (BMI) in river systems. The estimates from the SEM showed that an increase in both urban and agricultural land use percentage directly increased the biochemical oxygen demand (BOD) and TP while decreasing the BMI of streams.…”
Section: Contributionsmentioning
confidence: 99%
“…Herein, I summarize the contributed papers in the context of eutrophication and related risks to the health of ecological systems to paint an overall picture of this Special Issue ( Table 1 ). Three studies focused on “eutrophication” [ 17 , 18 , 19 ], four on “ecological health risk” [ 20 , 21 , 22 , 23 ], and a further three papers on “ecosystem health and services” [ 24 , 25 , 26 ] have been included in this issue. A more detailed summary of all articles is offered in the following section.…”
Section: Introductionmentioning
confidence: 99%